2006
DOI: 10.4141/a05-059
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid and vitamin B12 in reproducing sows: New concepts

Abstract: Matte, J. J., Guay F. and Girard, C. L. 2006. Folic acid and vitamin B 12 in reproducing sows: New concepts. Can. J. Anim. . In pig nutrition, the present gaps in the information on B-complex vitamins have important implications for empiricism and disparities in dietary recommendations. This is particularly true for folic acid (B 9 ) and vitamin B 12 . Recent studies suggest that the beneficial effects of B 9 on sow prolificacy may be due to enhanced embryo development and survival. Embryo synthesis of estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
(76 reference statements)
0
10
0
7
Order By: Relevance
“…Such differences between studies suggest a parity effect as it has been reported in previous studies carried out during early gestation of sows (Guay et al, 2002). Matte et al (2006) hypothesized that B 12 requirements would be greater in nulliparous sows because of the dual needs for reproduction and for growth and development as compared to reproduction only in mature sows.…”
Section: Sow Metabolismmentioning
confidence: 80%
“…Such differences between studies suggest a parity effect as it has been reported in previous studies carried out during early gestation of sows (Guay et al, 2002). Matte et al (2006) hypothesized that B 12 requirements would be greater in nulliparous sows because of the dual needs for reproduction and for growth and development as compared to reproduction only in mature sows.…”
Section: Sow Metabolismmentioning
confidence: 80%
“…CV: coeficiente de variação, R0: ração controle, R1: ração contendo 0,2% betaína e redução de 50% da exigência para metionina digestível, R2: ração controle com suplementação de 0,2% de produto comercial contendo betaína, R: ração, C: ciclo, NS: não significativo e *: significativo Não foram observadas diferenças significativas para as variáveis: nascidos totais, nascidos vivos, natimortos, mumificados, mortalidade e desmamados. Considerando os efeitos prejudiciais da homocisteína, um metabólito da metionina, sobre o transporte placentário de aminoácidos (JANSSON, 2009) e quando encontrada em níveis elevados pode causar perda gestacional e um prejuízo no desenvolvimento dos fetos (IKEDA et al, 2010;MATTE;GUAY;GIRARD, 2006), uma possível ação positiva da betaína como doador de grupos metil estaria relacionada a redução nos níveis de homocisteína por meio da metilação desta, promovendo o crescimento e a maturação dos conceptos menos desenvolvidos, permitindo maior sobrevivência até o parto (RAMIS et al, 2011;VAN WETTERE;HERDE;HUGHES, 2012); no entanto, as duas formas de inclusão de betaína avaliadas no presente estudo não promoveram tais efeitos, possivelmente devido ao fato das rações terem sido formuladas com base na exigência mínima para metionina digestível para porcas.…”
Section: Resultsunclassified
“…Nesse sentido, a betaína natural é um aditivo extraído da beterraba que atua como osmólito, diminuindo a demanda energética do suíno para manter uma adequada hidratação celular e o correto equilíbrio iônico. Além disso, a betaína apresenta-se como fonte de grupos metil, importante para a conversão de homocisteína em metionina, cuja elevada concentração do primeiro pode prejudicar o desenvolvimento embrionário e aumentar a mortalidade pós-natal (MATTE; GUAY; GIRARD, 2006). Esta forma de atuar da betaína promove uma economia de energia de manutenção para o suíno, além de menor necessidade de doadores de grupos metil de maior custo, tais como a DL-metionina e a colina.…”
Section: Introductionunclassified
“…Previous studies found that dietary supplementation with 15 mg/kg of folic acid [17], 3 g/kg of betaine [18], 1650 mg/kg choline [19,20] or 150 μg/kg VB12 [21] was effective in increasing sow litter size, and significantly reduced homocysteine levels in plasma.…”
Section: Methodsmentioning
confidence: 99%